The Relationship between Career Development and Employee Performance in the Banking Sector in Kenya (African Multidisciplinary Journal of Research, 2025)
The study investigated the link between career development and employee performance in Kenya's banking sector. It highlighted the importance of understanding factors that enhance employee performance for organizational goals and competitiveness. Career development can impact employee motivation, job satisfaction, and overall performance. The aim was to understand how career development initiatives influence employee performance, providing insights to optimize human resource management practices in the banking sector. The study involved 127 Kenyan commercial bank employees, collected through structured questionnaires. The research focused on career development practices like professional training, career progression opportunities, mentoring, and performance feedback. The study used regression analysis and diagnostic tests to determine the relationship between career development and employee performance, aiming to understand the strength and direction of this relationship. Diagnostic tests were conducted to assess the regression model's robustness, revealing no significant multicollinearity in the independent variables using the Variance Inflation Factor. The Kolmogorov-Smirnov test confirmed normality of data, while the Breusch-Pagan test confirmed heteroskedasticity, indicating no issues with variance instability. Lastly, the Breusch-Godfrey test confirmed the absence of serial correlation in the model, allowing the Ordinary Least Squares (OLS) regression analysis to be used. The study revealed a strong positive correlation between career development and employee performance. It suggested that practices like training programs, career advancement opportunities, and mentoring can significantly improve employee performance. Employees who feel supported in their career development are more motivated, committed, and productive. Career development has the most significant impact on performance. The study's focus on the Kenyan banking sector provided valuable insights into the importance of investing in human capital development for organizational outcomes. It suggested that banking institutions should prioritize career development programs to improve employee engagement and performance. The study also recommended that policymakers in the banking sector create frameworks to incentivize and support career development initiatives.